Child: “I don’t Understand – We didn’t Learn that in Kindergarten!” - HILČENKO, SLAVOLJUB; NIKOLIĆ, SANJA (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2023)
By the end of 2022, Serbia transformed its preschool education system, transitioning from a traditional approach to a project-based learning approach. However, if this transformation remains limited to preschool education without coordinated changes in learning at lower (and even higher) grades of elementary school in the next 4–8 year cycle, teachers, children, and their parents will be most affected. We believe that the new project-based approach to learning for children will not provide adequate fundamental and systematic knowledge in many scientific fields, including mathematics methodology (e.g., spatial and temporal relationships, arithmetic, number concept, ratios, fractions, geometry…). The consequences will not only be visible in their further education but also in their inadequate preparation to navigate their environment and understand space, time, relationships, and other mathematical concepts. This is what the educators' survey results are talking. The aim of this paper is to highlight possible problems since the Government of the Republic of Serbia and the Ministry of Education have not suggested a linear reform of these education levels.